2012
DOI: 10.1051/0004-6361/201219140
|View full text |Cite
|
Sign up to set email alerts
|

Optical photometric and spectral study of the new FU Orionis object V2493 Cygni (HBC 722)

Abstract: Aims. We present new results from optical photometric and spectroscopic observations of the eruptive pre-main sequence star V2493 Cyg (HBC 722). The object has continued to undergo significant brightness variations over the past few months and is an ideal target for follow-up observations. Methods. We carried out CCD BVRI photometric observations in the field of V2493 Cyg ("Gulf of Mexico") from August 1994 to April 2012, i.e. at the pre-outburst states and during the phases of the outburst. We acquired high, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 25 publications
3
46
0
1
Order By: Relevance
“…Optical monitoring of the source prior to the outburst (Miller et al 2011;Semkov et al 2012) revealed that what appears as the starting point of the outburst in Fig. 1 in 2010 May is already an elevated flux level compared to the brightness of the source before 2010.…”
Section: Results and Analysismentioning
confidence: 99%
“…Optical monitoring of the source prior to the outburst (Miller et al 2011;Semkov et al 2012) revealed that what appears as the starting point of the outburst in Fig. 1 in 2010 May is already an elevated flux level compared to the brightness of the source before 2010.…”
Section: Results and Analysismentioning
confidence: 99%
“…The CCD photometric observations were performed with the 2 m RCC, the 50/70 cm Schmidt and the 60 cm Cassegrain telescopes of the National Astronomical Observatory Rozhen (Bulgaria) and the 1.3 m RC telescope of the Skinakas Observatory 1 of the Institute of Astronomy, University of Crete (Greece). More observational and technical details are given in Semkov et al (2012). All frames were exposed through a set of standard Johnson-Cousins filters.…”
Section: Star Sample and Measurementsmentioning
confidence: 99%
“…Since Herbig's (1958) discovery, it has been known to contain a number of PMS stars, among which are T Tauri and Hα emission stars, Herbig-Haro objects, and flare stars from the UV Ceti type (Armond et al 2011;Semkov et al 2012;Findeisen et al 2013). The largest number of young stars are found in the so-called Pelican Nebula (IC 5070), a few in the North America (NGC 7000) near "Florida", and in the "Gulf of Mexico" region between the two nebulas (Corbally et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This new FUors was ideal to study the physical state of the protostellar envelope right after the outburst. The optical photometric variability was analyzes, and the large amplitude outburst and re-brightenig were clearly observed (Semkov et al 2012;Green et al 2011). Lee et al (2011) presented the high resolution optical spectroscopic evolution of HBC 722 which showed the early stages of a FUors outburst.…”
Section: Introductionmentioning
confidence: 94%
“…5400 5600 5800 6000 6200 6400 6600 JD (+2,450,000) , crosses are from , and plus signs are from (Antoniucci et al 2013). The BV RI data are from (Semkov et al 2012) and the AAVSO data archive.…”
Section: Observationmentioning
confidence: 99%